PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT. PERUSAHAAN LISTRIK NEGARA (PLN PERSERO) ULP PERBAUNGAN - Hasibuan, Nurmaliza Almira; Syafrizal, Syafrizal; Yudha, Tri Kartika (Universitas Pahlawan Tuanku Tambusai, 2025)
The problem statement in this research is whether motivation and work environment affect the performance of employees at PT. PLN Persero ULP Perbaungan. The purpose of this study is to determine the extent of the influence of motivation and work environment on employee performance at PT. PLN Persero ULP Perbaungan. This research employs a quantitative approach, with a population and sample of 75 employees. The analytical tool used in this study is SPSS Version 22, and the data analysis technique applied is multiple linear regression analysis, including data quality testing, classical assumption testing, and hypothesis testing. Based on the research findings, it is concluded that motivation has a positive and significant effect on employee performance at PT. PLN Persero ULP Perbaungan. Likewise, the work environment also has a positive and significant effect on employee performance. Therefore, both motivation and work environment positively and significantly influence employee performance at PT. PLN Persero ULP Perbaungan. Keywords: Motivation, Work Environment, Employee Performance.